Unique Presentation of Rosai-Dorfman Disease as Concomitant Appendiceal and Rectal Masses with IgG4-Positive Plasma Cells Diagnosed by Core Needle Biopsy - Jenna J. Poldemann; Benjamin H. Hinrichs; Abouelmagd Makramalla (Case Reports in Oncological Medicine)
Rosai-Dorfman disease (RDD), or sinus histiocytosis with massive lymphadenopathy, is a rare non-Langerhans cell histiocytosis. We report a case of a 69-year-old male with concurrent appendiceal and rectal masses who underwent CT-guided percutaneous biopsy. Histopathology confirmed a diagnosis of RDD with IgG4-positive plasma cells. It is believed to be a subset of RDD that shares similar features with IgG4-related disease suggesting some overlap of the two diseases. Because gastrointestinal RDD accounts for less than 1% of extranodal disease, it is important to recognize this entity in order to guide management. We review the presentation, diagnosis, and treatment of gastrointestinal RDD and discuss the possible overlap with IgG4-related disease.